To Investigate the Effects of Nicotine on Morphology of an In-Vitro Reconstituted Model of Normal Healthy Uninflamed Oral Mucosa (Medical Forum Monthly, 2024)
Objective: The objective of this study was to investigate the effect of nicotine on morphology of an uninflamed reconstituted oral mucosa in vitro when treated for 5 minutes and 24 hours respectively. Study Design: Observational study. Place and Duration of Study: This study was conducted at the Department of Oral Pathology Bart’s and the London Queen Mary School of Med. and Dentistry Queen Mary, University of London from July 2018 to July 2019. Materials and Methods: This study focuses on the effects of nicotine on an in vitro reconstituted model of oral mucosa. The reconstituted human epithelium model used in this study was prepared and supplied by Skin Ethic Laboratories, Nice, France. The effect of the different treatments of nicotine on tissue morphology was assessed using formalin fixed paraffin wax sections and heamatoxylin and eosin staining. Results: It was found that the effect of nicotine after 5 minutes and 24 hours with working solutions (10μM and 1mM) used on uninflamed oral mucosal did not significantly effect on the gross morphology. Conclusion: This study has confirmed that all the concentration of nicotine used after 5 minutes and 24 hours had no effect on tissue morphology.